2022
DOI: 10.3390/su142114116
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Solar Stills via Hollow Cylindrical Perforated Fins, Inclined Rectangular Perforated Fins, and Nanocomposites: An Experimental Investigation

Abstract: A practical study was conducted to improve the performance of conventional pyramidal solar stills (CPSS) using two types of fins with differing geometries, as well as nanocomposites of TiO2 and graphene. The first fin was hollow, cylindrical, and perforated (HCPF), whereas the second fin was an inclined perforated rectangular fin (IPRF). The fins were integrated with the base of a solar still to evaluate their performance in comparison with a CPSS. The obtained experimental results demonstrated that the pyrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The latent heat capability varies between zero (for a solid) and one (for a liquid), and the liquid fraction ( β ) can be expressed as [ 21 , 22 ]. …”
Section: Numerical Proceduresmentioning
confidence: 99%
“…The latent heat capability varies between zero (for a solid) and one (for a liquid), and the liquid fraction ( β ) can be expressed as [ 21 , 22 ]. …”
Section: Numerical Proceduresmentioning
confidence: 99%
“…For the purpose of implementing energy efficiency, the ratio of solar irradiation to evaporative heat transfer on the absorber plate is used to calculate the SSD overall thermal efficiency [36,37].…”
Section: Thermal Efficiency Of Ssdmentioning
confidence: 99%
“…The experimental results indicated that maximum daily production of 32.3% improvement was obtained with sponge and sand. Suha et al [41] conducted experimental study to evaluate the influence of inclined rectangular perforated fins, hollow cylindrical perforated fins, and nanocomposites on the yield of a pyramid solar stills. The results indicated that, inclined rectangular perforated fins and hollow cylindrical perforated fins, improving the productivity by 55.9% and 31.3%, respectively, compared to that of the conventional PSS.…”
Section: Introductionmentioning
confidence: 99%